Association of Serum Uric Acid Levels in Patients with Acute Ischemic Stroke and Clinical Outcome - Tabassum, Muhatarima; Uddin, Md Kafil; Ali, Md Ahmed; Haque, SM Emdadul; Kabir, Md Raseul; Pramanik, Md Amjad Hossain (TAJ: Journal of Teachers Association, 2022)
Background: Stroke is one of the most common, most fatal, and debilitating neurologic diseases. Numerous risk factors are involved in the development of strokes, such as hypertension, cigarette smoking, hyperlipidemia, and diabetes. In addition, other factors may influence the disease's development or course, like uric acid serum level. Objective: To determine the association between serum uric acid (SUA) levels in patients with acute ischemic stroke and clinical outcomes. Material and method: This was a longitudinal descriptive study carried out among one hundred and twenty consecutive patients with acute ischemic stroke (AIS) admitted to the Department of Neuromedicine, Rajshahi Medical College Hospital ( during a period of two years from July'2015 to July' '2017 were included in the study. 12.11 years. Of 120 patients with AIS, 60.8% were male, and 39.2% were female. The study revealed that AIS patients with high SUA levels have significantly lower Glasgow Coma Scale (GCS) scores in comparison to normal SUA levels (p<0.001). There is also a considerably higher modified Rankin Score (mRS) at discharge (4.02 ± 1.47), at one month (4.03 ± 1.01), and at three months (4.21 ± 1.12) (p< 0.001). Thus in our study, mRS analysis showed a significant clinical deterioration in patients with high SUA levels. A comparison of clinical outcomes of AIS patients by MRS between high and normal SUA levels revealed that at three months of follow-up, there is significant deterioration in patients with high SUA levels (p<0.001). There was significantly less improvement with high SUA levels (p<0.001).In this study, a total of 20 patients died at different intervals; at discharge (11), at one month (3), and three months (6). The study showed that patients with high SUA levels had significantly increased mortality in comparison to patients having normal SUA levels. It was statistically significant at discharge and one month (p<0.01 and p<0.05) but not significant at three months (p>0.05). Conclusion: A significant association was found between high serum uric acid levels and the clinical outcome of AIS patients. Estimation of serum uric acid offers a simple, inexpensive, quick, and non-invasive method for identifying such high-risk patients. TAJ 2022; 35: No-1: 63-69